Genome-wide association analysis reveals the optimal genomic regions for pod size in bean - Li, Mao; Wu, Xinyi; Wang, Baogen; Wu, Xiaohua; Wang, Ying; Wang, Jian; Dong, Junyang; Wu, Jian; Lu, Zhongfu; Sun, Yuyan; Dong, Wenqi; Yang, Jing; et al. (Frontiers in Plant Science, 2023)
The snap bean is the most important vegetable legume worldwide. Pod size is an important yield and appearance quality trait. However, the improvement of pod size in snap bean had been largely hindered in China due to lack of available genes controlling pod size. In the current study, we collected 88 snap bean accessions and evaluated their pod size traits. Through genome-wide association study (GWAS), 57 SNPs significantly associated with pod size were detected. Candidate gene analysis showed that cytochrome P450 family genes, WRKY and MYB transcription factors were the predominant candidate genes for pod development, and 16 of the 66 candidates showed relatively higher expression pattern in flowers and young-pods. A significant pod length SNP and a single pod weight SNP were successfully converted into KASP markers and validated in the panel. These results contributed a better understanding of the genetic basis of pod size, and also provided gene resources for molecular breeding of pod size in snap bean.